2022
DOI: 10.1021/acs.chemmater.2c02104
|View full text |Cite
|
Sign up to set email alerts
|

ACuZrQ3 (A = Rb, Cs; Q = S, Se, Te): Direct Bandgap Semiconductors and Metals with Ultralow Thermal Conductivity

Abstract: ACuZrQ 3 (A = Rb, Cs; Q = S, Se, Te) were synthesized as black platelet crystals. RbCuZrS 3 , RbCuZrSe 3 , and CsCuZrS 3 crystallize in the KCuZrSe 3 structure type with space group Cmcm, and RbCuZrTe 3 and CsCuZrTe 3 crystallize in the lower symmetry space group Pnma. The tellurides exhibit a secondorder Jahn−Teller distortion with off-centering of Zr in its octahedral environment. The magnitude of the distortion is larger in RbCuZrTe 3 than in CsCuZrTe 3 . The structures of β-CsCuS 4 and Rb 2 Cu 5 Te 5 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…A similar ultralow thermal conductivity value of ∼0.35 W m −1 K −1 at 573 K is reported for the structurally related RbCuZrTe 3 . 12 The rattling of relatively loosely bound Rb + cations and the distortion of Zr-coordinated octahedra in RbCuZrTe 3 are responsible for the ultralow value of the lattice thermal conductivity ( k lat ). On similar lines, it is expected that the rattling of Ba 2+ cations in the BaCeCuS 3 sample at high temperatures should also lead to low values of k lat .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar ultralow thermal conductivity value of ∼0.35 W m −1 K −1 at 573 K is reported for the structurally related RbCuZrTe 3 . 12 The rattling of relatively loosely bound Rb + cations and the distortion of Zr-coordinated octahedra in RbCuZrTe 3 are responsible for the ultralow value of the lattice thermal conductivity ( k lat ). On similar lines, it is expected that the rattling of Ba 2+ cations in the BaCeCuS 3 sample at high temperatures should also lead to low values of k lat .…”
Section: Resultsmentioning
confidence: 99%
“…15 The Kanatzidis group recently reported six new compounds of the 1113family with a general formula of ACuZrQ 3 (A = Rb, Cs; Q = S, Se, and Te). 12 An ultralow thermal conductivity value of B0.35 W m À1 K À1 was observed for a polycrystalline sample of RbCuZrTe 3 at 573 K. The ultralow thermal conductivity of this compound was attributed to the rattling of Rb + cations in the structure at high temperatures.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Advances in synthetic chalcogenide chemistry have accelerated the discovery of functional materials as well as stimulated the development of numerous technological applications for these materials, all helped by an increased understanding of composition–property relationships. , Chalcogenide-based compounds occupy a unique position in material chemistry due to the soft nature of the chalcogen elements and emerging covalent metal chalcogenide bonding, which results in a rich and diverse crystal chemistry. , In fact, the electronic structure of chalcogenide materials favors their applications as quantum materials, catalysts, ion-exchange materials, ion-conductors, luminophores, thermoelectric materials, and semiconductors. Recent advances in developing convenient synthetic approaches have enabled the rational synthesis of new functional chalcogenide-based materials containing a wide range of elements, resulting in various material types, ranging from nanoparticles to large single crystals of pure inorganic compositions and hybrid structures. Another new material type that has emerged from these investigations is salt-inclusion chalcogenide materials (SICs) , that exhibit novel framework topologies and possess ionic inserts (salt-inclusions).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other well-known mechanisms, the off-centering effect has been rarely discussed. However, recent research has shown that the off-centering effect could introduce low frequency optical mode and result in strong acoustic-optical (A-O) phonon scattering, making it an effective approach to reduce the thermal conductivity [39][40][41][42].…”
mentioning
confidence: 99%